Autologous fat transfer with SEFFI (superficial enhanced fluid fat injection) technique in periocular reconstruction. (4th May 2018) - Riesco, Benjamin; Abascal, Cristina; Duarte, Ana; Flores, Rocio Mariel; Rouaux, Guillermina; Sampayo, Raul; Bernardini, Francesco; Devoto, Martin
ABSTRACT: Purpose : To evaluate the aesthetic and functional outcomes of autologous fat transfer using the SEFFI (superficial enhanced fluid fat injection) technique for reconstruction of the periocular area. Methods : Autologous fat injections prepared with the 0.5 mL and 0.8 mL SEFFI technique were used in four patients for periocular rehabilitation. Results : Case 1 (C1): A patient with left-sided progressive facial hemiatrophy underwent ipsilateral volumizing with 0.8 SEFFI in the superior, temporal, and inferior periorbital areas, and 0.5 SEFFI in both eyelids. C2: A 21-year-old female with a post trauma frontal scar, left ptosis, and lower eyelid retraction was treated with 0.5 SEFFI applied in the scar area associated with an upper eyelid conjunctivomullerectomy and resection of the lower eyelid retractors. C3: A patient with previous left-eye evisceration and orbital floor and medial wall fractures underwent socket reconstruction with buccal mucosal graft in the lower fornix and 0.5 SEFFI injections in both superior and inferior eyelids. SEFFI was also applied in the intraorbital space for correction of the enophthalmos. C4: A patient with lower lid retraction post blepharoplasty was treated with 0.8 SEFFI injections in lower eyelids and malar areas, complemented with a bilateral lateral cantopexy. Conclusions : Autologous fat transfer with SEFFI technique is an effective and safe procedure in cases of periocular rehabilitation.